A new dimeric carbazole alkaloid from Murraya koenigii (L.) leaves with α-amylase and α-glucosidase inhibitory activities. (December 2022) - Sampath, Sepala Nupage Thushara Indika; Jayasinghe, Susanthi; Attanayake, Anoja Priyadarshani; Karunaratne, Veranja; Yaddehige, Mahesh Loku; Watkins, Davita L.
Abstract: A new dimeric carbazole alkaloid, 3, 3′, 5, 5′, 8-pentamethyl-3, 3′-bis(4-methylpent-3-en-1-yl)-3, 3′, 11, 11′-tetrahydro-10, 10′-bipyrano[3, 2- a ]carbazole, was isolated from the hexane extract of leaves of Murraya koenigii (L.) Sprengel. (Family: Rutaceae). The structure was elucidated based on 13 C and 1 H NMR, High-Resolution Mass Spectrometry (HRMS), and 2D NMR data. The in vitro antidiabetic activity of the new dimer was investigated in terms of α-amylase and α-glucosidase enzyme inhibition assays. The dimer exhibited significant α-amylase inhibitory activity (IC50 = 30.32 ± 0.34 ppm) and α-glucosidase inhibitory activity (IC50 = 30.91 ± 0.36 ppm). Graphical Abstract: ga1 Highlights: New dimeric asymmetric carbazole alkaloid was identified from fresh leaves of Murraya koenigii . The new dimer has two different monomeric units connected at C-10 and C-10′. The new compound exhibits significant α-amylase and α-glucosidase inhibitory activity. And thus could be a potential lead compound for treatment of diabetes.